2013
DOI: 10.1063/1.4815941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disorder on carrier transport in ZnO thin films grown by atomic layer deposition at different temperatures

Abstract: We have grown $200 nm thick ZnO films on (0001) sapphire substrates using atomic layer deposition at different substrate temperatures ranging from $150 to 350 C. X-ray diffraction and photoluminescence spectra of these films showed that crystalline and compositional native defects were strongly dependent on the substrate temperature. Room temperature Hall measurement showed that all the films were degenerate with carrier concentration exceeding the Mott's critical density n c required for metallic conduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Negative MR in TCO is often observed in the weak localization regime. Furthermore, such cases are usually observed at low temperatures [15,24]. An understanding of the experimental data based on the WL model requires the existence of extended states at low temperatures.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Negative MR in TCO is often observed in the weak localization regime. Furthermore, such cases are usually observed at low temperatures [15,24]. An understanding of the experimental data based on the WL model requires the existence of extended states at low temperatures.…”
Section: Methodsmentioning
confidence: 97%
“…Disorder in semiconductors can be created by film growth [23][24][25] or doping [26]. In disordered semiconductors, where there is a large amount of impurities or defects, electrons in diffuse mode can have multiple scatterings from impurities or defects without a loss of energy that is the elastic collision.…”
Section: Introductionmentioning
confidence: 99%
“…This additional oxygen in the form of OH groups can act as acceptors thereby reducing the electron concentrations [13,14]. On the contrary when growth temperature was increased beyond 200°C, oxygen vacancy and Zn interstitial related defects may be created due to decomposition of precursors on heated substrate surface [13,15]. These defects are donor type defects which can increase the electron concentration in the ensuing ZnO films [1,15].…”
Section: C-v Characterization and Analysismentioning
confidence: 99%
“…On the contrary when growth temperature was increased beyond 200°C, oxygen vacancy and Zn interstitial related defects may be created due to decomposition of precursors on heated substrate surface [13,15]. These defects are donor type defects which can increase the electron concentration in the ensuing ZnO films [1,15]. Moreover some first principle theoretical studies have revealed that Hydrogen may be a potential donor in ZnO [25], but according to experimental studies of Guziewicz et al Hydrogen does not act as a dominant donor in ZnO thin films grown by ALD [26].…”
Section: C-v Characterization and Analysismentioning
confidence: 99%
See 1 more Smart Citation